Fungsi Masjid dari Masa Ke Masa Dalam Perspektif Al-Qur’an - Mohamad Ghozi (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2019)
The mosque, if it is known, is both Muslim and non-Muslim. Everyone who listens to these words must have been pictured in his mind somewhere, where people perform rituals of prayer, chanting, listening to tausiah and the like. The mosque today is very different from the mosque at the time of the founding of Islam. The mosque at the time of the Prophet Muhammad SAW, was an inseparable part of the development of the Islamic religion. Because the mosque is the center of the development of Islam itself. In this paper, the author wants to explain a little to the reader to better understand, the mosque has a very vital role in the progress of Islamic civilization. By understanding the function and role of the mosque, it is hoped that we will further prosper the mosque, so that the progress of Islam that once started in the mosque will be repeated in the present.